Pengaruh Motivasi Guru terhadap Prestasi Belajar Siswa di MI Yadinu Pancor Kopong Lombok Timur - Wardiana, Wina; Asroyani, Asroyani (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This study aims to determine whether there is an influence of motivation on student achievement at MI Yadinu V Pancor Kopong district. Pringgasela Kab. East Lombok. The population in this study were all students at MI Yadinu V Pancor Kopong, with the number of students being 170 people, with a sample size of 31 people. In this study, data collection was carried out using questionnaires and documentation to determine student achievement. The data then used descriptive analysis and simple regression analysis. Based on the results of the study for the results of the analysis using simple regression, the t-test increased the number of t count by 3,342 > t table = 1,696, this indicates that Ho is rejected and Ha is accepted, that is, good teacher motivation can affect student achievement. Therefore, it is important for teachers to motivate students in learning so that students have broad insight and knowledge, because with motivation, students will be encouraged to continue learning so that it can affect student achievement.